Heritage Stones Through Ages and Civilizations: A Comparative Study of Western Ghats Laterite (India) and Tezontle Volcanic Scoria (Mexico) - Bobby P. Mathew; Carles Canet; Elizabeth Lozada-Amador; Gurmeet Kaur; Raymond A. Duraiswami; Elizabeth Castañeda-Bastida; Francisco O. Lagarda-García (Geoheritage, 2026)
A comparison is made between two IUGS Heritage Stones designated in 2024, Western Ghats Laterite (India) and Tezontle volcanic scoria (Mexico), to highlight their cultural impact across millennia and analyze a possible convergence in their use and symbolism. These stones originate from contrasting cultural settings and were generated through distinct geological processes and timescales. In both cases, they exhibit extensive, long-standing use in cultural heritage and are deeply rooted in local identity. Laterite is a residual product formed in situ through prolonged chemical weathering under humid tropical conditions, whereas tezontle is a highly vesicular volcanic scoria generated by Strombolian eruptions. From an aesthetic perspective, there is a significant coincidence based on their predominant reddish coloration and rough, matte surfaces. However, their resemblance in terms of mechanical properties, such as compressive strength and density, is notably lower; consequently, their technical applications differ in each case. A striking convergence exists in how architectural practices in both regions leveraged the favorable workability and aesthetic properties of these stones to achieve comparable results; both stones were paired with lighter materials to achieve visual contrast in intricate ornamentation set against the sober, dominant reddish-dark hue of the façades. This was particularly prominent during the Baroque period (16th–18th centuries), imprinting a distinct identity upon both regions through shared elements arising from the confluence of colonialism and deep-rooted indigenous cultures. Consequently, the use of these respective stones serves as an element of material continuity, acting as a tangible bridge between colonial influence and native heritage. The designation as an IUGS Heritage Stone is strengthened by the prior recognition of World Heritage properties featuring these stones, creating a synergy that enhances the connections between cultural and geoheritage. This joint recognition should foster cohesive conservation policies prioritizing original restoration materials, the protection of historical quarries, and the development of geotourism.